3 - Can Africa Make Use of the New Aid Architecture? - Wohlgemuth, Lennart (Africa Development, 2021)
In 2005, an agreement was reached in Paris between a large number of donor countries and institutions and recipient countries on how to make aid more efficient. This new agreement, called the Paris Declaration, if it is handled rightly, can open up increased ownership of their development agenda for the recipient countries. The agreement is in itself nothing new – it contains ingredients that had been discussed since the 1970s and agreed upon a number of times. The newness is that a number of recipient countries were active in developing the underlying concepts and that there is the opportunity, for those who can take it, of seizing the initiative in the development dialogue. This article argues that the agreement will not lead to automatic improvement but will require the active participation of the host countries.